1987
DOI: 10.1002/lsm.1900070107
|View full text |Cite
|
Sign up to set email alerts
|

Bone fracture consolidates faster with low‐power laser

Abstract: Low-power laser radiation is currently used in the treatment of pain and osteoarticular inflammation. However, the mechanisms of the laser biostimulating effects on tissue are still not completely understood. With laser treatment, we have achieved activation of osseous regeneration in human bone fractures. After 7 years of positive clinical control in human beings, we decided to start an experimental study of fractures in the tibia of mice, histologically controlling its reparation after exposure to 632 nm. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
107
1
18

Year Published

1996
1996
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 232 publications
(132 citation statements)
references
References 4 publications
6
107
1
18
Order By: Relevance
“…For example, a total of 4.0 joules laser energy applied on experimentallyinduced skin incisions [39] or skin defects in rats [30], produces faster collagen synthesis as judged by assaying 14 C glycine and 3H proline or 3H hydroxyproline [30,39]. Similarly, fractures induced in the radii of 44 New Zealand rabbits, irradiated daily with 236 mW cm -2 CO 2 laser for 10 minutes on 10 successive days have been shown to heal faster than controls [40] as do mice tibial fractures irradiated with low intensity He-Ne laser [41].…”
Section: Effects Of Laser Photostimulationmentioning
confidence: 99%
“…For example, a total of 4.0 joules laser energy applied on experimentallyinduced skin incisions [39] or skin defects in rats [30], produces faster collagen synthesis as judged by assaying 14 C glycine and 3H proline or 3H hydroxyproline [30,39]. Similarly, fractures induced in the radii of 44 New Zealand rabbits, irradiated daily with 236 mW cm -2 CO 2 laser for 10 minutes on 10 successive days have been shown to heal faster than controls [40] as do mice tibial fractures irradiated with low intensity He-Ne laser [41].…”
Section: Effects Of Laser Photostimulationmentioning
confidence: 99%
“…Estudos que utilizaram radiação de laser hélio-neô-nio mostraram efeitos benéficos na osteogênese 34,50 com aumento na vascularização e aceleração na razão de formação óssea.…”
Section: Laserunclassified
“…Several reports have shown that low-level laser irradiation (LLLI) stimulates bone regeneration 1,2) . In bone metabolism, in vivo experimental models using biochemical and quantitative histomorphometrical experiments have revealed that LLLI stimulates alkaline phosphatase activity, calcium accumulation and the rapid accumulation of reparative new bone in injuries in rat tibia 3,4) .…”
Section: Introductionmentioning
confidence: 99%